تقنيات التحقيق المحاسبي في إطار الرقابة الجبائية دراسة ميدانية بمركز الضرائب بولاية الاغواط - بوبكراوي خالد; حساب محمد لمين (جامعة عمار ثليجي الاغواط, 2022)
This Study aims to show and to high light the techniques used in the accounting auditing within the frame work of compulsory control and how to embody them on the ground in addition to getting to know how to have rights and obligations of both tax payer and the tax administration through the compliance, and his way shows the punishments that are imposed on them through the examination of the accountability of the tax payer and compare it within the introduction of his party where it helps to detect tax evasion and activate tax control through the process of accounting investigation which is a form of it and extract results and reach solutions.